2011
DOI: 10.1007/s00595-010-4474-y
|View full text |Cite
|
Sign up to set email alerts
|

Goblet cell carcinoid of the rectum with lymph node metastasis: Report of a case

Abstract: We report an unusual case of goblet cell carcinoid (GCC) of the rectum. A 75-year-old man was admitted to our hospital with anal bleeding, and a hard tumor was felt on the anterior wall of the lower rectum during rectal examination. We performed colonoscopy, and found a 30-mm type 2 tumor in the lower rectum and anal canal. Histological examination of biopsies revealed rectal adenocarcinoma. Based on these findings, we diagnosed rectal adenocarcinoma and performed Miles' operation with lymph node dissection. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The rectum is an unusual site for GCC, and less than 10 cases of GCC arising in the rectum have been reported [6]. Among them, there have been no patients with NF-1 as the present case, while a NF-1 patient with appendiceal GCC was recently described [7].…”
Section: Discussionmentioning
confidence: 87%
“…The rectum is an unusual site for GCC, and less than 10 cases of GCC arising in the rectum have been reported [6]. Among them, there have been no patients with NF-1 as the present case, while a NF-1 patient with appendiceal GCC was recently described [7].…”
Section: Discussionmentioning
confidence: 87%
“…Carcinoid-related tumors are classified as carcinoid (well-differentiated neuroendocrine neoplasm) and mixed endocrine-exocrine carcinoma by the World Health Organization histological classification of tumors of the appendix. The latter includes tubular carcinoid, GCC (mucinous carcinoid), and mixed carcinoid adenocarcinoma [7]. Höfler et al reported that GCCs are derived from undifferentiated stem cells and are different from typical carcinoids that originate from enterochromaffin cells (Kulchitsky) in the mucosal stroma [8].…”
Section: Discussionmentioning
confidence: 99%
“…There are rare cases of ostensibly primary extra-appendiceal GCC have been reported as stomach, duodenum, ampulla of Vater (21), jejunum, ileum, cecum, splenic flexure (22,23), ascending colon (24) and rectum (22,25,26,27,28).…”
Section: Mcdole Et Al From Washington University Inmentioning
confidence: 99%